Semitransparent Polymer Solar Cells Based on Liquid Crystal Reflectors - Shaopeng Yang; Tiening Wang; Xiaohui Zhao; Luo Gu; Qiman Yang; Guang Li; Xiaowei Li; Guangsheng Fu (International Journal of Photoenergy)
The effects of liquid crystal (LC) reflectors on semitransparent polymer solar cells (PSCs) were investigated in this paper. By improving the cathode, we manufactured semitransparent PSCs based on the conventional PSCs. We then incorporated the LC reflector into the semitransparent PSCs, which increased the power conversion efficiency (PCE) from 2.11% to 2.71%. Subsequently adjusting the concentration and spinning speed of the active layer material changed its thickness. The maximum light absorption for the active layer was obtained using the optimum thickness, and the PCE eventually reached 3.01%. These results provide a reference for selecting LC reflectors that are suitable for different active layer materials to improve the PCE of semitransparent PSCs.